Rhinoceroses Are Awesome! - Allan Morey (Oxford, United Kingdom Capstone Global Library Ltd, 2015)
Boom! When rhinoceroses move, the ground shakes! These tanks with horns are one of the world's largest land animals. Engaging text, bold photos, and colorful maps shine a spotlight on these mighty pachyderms. Readers are introduced to physical features, behavior, habitat, and life cycle to find out why rhinoceroses are awesome!
Keywords: PY-UOI-How the World Works + Non Fiction -- PY-UOI-How the World Works + Non Fiction; Endangered Species; Endangered Species